1989
DOI: 10.1016/0014-5793(89)81588-1
|View full text |Cite
|
Sign up to set email alerts
|

Activation of protein kinase C alters the interaction of α2‐adrenoceptors and the inhibitory GTP‐binding protein (Gi) in human platelets

Abstract: The effect of 12-tetradecanoyl phorbol 13-acetate (TPA) on the hormonal modulation of adenylate cyclase was studied. The effect of epinephrine (a,-adrenergic action) was markedly diminished in membranes from TPA-treated platelets as compared to the controls. Interestingly, the inhibitory effect of guanylyl imido diphosphate (Gpp(NH)p) was not altered. Neither the number of 3-adrenoceptors nor their affinity for PH]yohimbine were affected by the treatment with TPA. In control platelets, 77% of the receptors wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

1991
1991
1995
1995

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…Further support for this interpretation was obtained in the binding studies [6]. Our current data are consistent with such an interpretation; they clearly show that the ¢ft'0ct of agents whose receptors activate the GTPase activity of Gi is markedly decreased.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Further support for this interpretation was obtained in the binding studies [6]. Our current data are consistent with such an interpretation; they clearly show that the ¢ft'0ct of agents whose receptors activate the GTPase activity of Gi is markedly decreased.…”
Section: Discussionsupporting
confidence: 90%
“…Further support for this interpretation was obtained in binding studies [6]; it was observed that in control platelets, approximately 75% of the receptors were m a high-affinity state for epinephrine and approximately 25°70 in a low-affinity state; Gpp(NH)p shifted the receptor affinity towards the low-affinity conformation [6]. In membranes from TPA-treated platelets, the receptors were in the low-affinity state and no further decrease in affinity was induced by Gpp(NH)p [6]. We examined the effect of TPA on hormone.stimulated GTPase activity; our results indicate that stimulation of PKC markedly diminished the hormone-stimulated GTPase activity of Gi.…”
Section: ! Introductionmentioning
confidence: 64%
See 3 more Smart Citations